Pulmonary Complications of Azanucleoside Therapy in Patients with Myelodysplastic Syndrome and Acute Myelogenous Leukemia - Molina, Manuel; Yellapragada, Sarvari; Mims, Martha; Rahman, Effie; Rivero, Gustavo (Case Reports in Hematology, 2015)
Our primary aim was to identify potential risk factors and clinical outcome of azanucleoside induced pulmonary complications in patients with myelodysplastic syndrome (MDS) and Acute Myelogenous Leukemia (AML). We present an 89-year-old female with MDS derived AML who developed fatigability, hypoxemia, and bilateral lung infiltrates indicating interstitial lung disease after 11 cycles of azanucleoside. In addition, we describe a cohort of six MDS patients with fever, cough, dyspnea, and pulmonary infiltrates at early time point during azanucleoside treatment. Early and late onset of pulmonary manifestations suggest different pathogenic mechanisms. Brief azanucleoside discontinuation and steroids led to rapid improvement in symptoms.